2018
DOI: 10.1142/s2424835518500303
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Upper Extremity Fractures

Abstract: Background: Venous thromboembolism (VTE) has been studied in lower extremity fractures but little is known of its relation with upper extremity (UE) fractures. As an often overlooked but serious complication, VTE may compromise patient outcomes. Methods: Using data on inpatients (aged ≥ 18 years) at a level-I trauma center and patients in the National Surgical Quality Improvement Program database who sustained UE fractures (clavicle, humerus, or radius/ulna) and VTE in the same hospitalization between 2007 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Both conservative and surgical treatment of clavicular fracture can be complicated by deep venous thrombosis (DVT). The estimated incidence of upper extremity DVT in children is 0.4 to 1 per 100,000 patients (10)(11)(12)(13)(14)(15). DVT in the upper limbs can be distinguished by 2 categories: primary and secondary (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both conservative and surgical treatment of clavicular fracture can be complicated by deep venous thrombosis (DVT). The estimated incidence of upper extremity DVT in children is 0.4 to 1 per 100,000 patients (10)(11)(12)(13)(14)(15). DVT in the upper limbs can be distinguished by 2 categories: primary and secondary (12).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical examination, duplex ultrasonography of the venous system and elevation of D-dimers are used for diagnosis of upper limb deep venous thrombosis (9)(10)(11)(12)(13)(14). Up to 50% of patients can be asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Hoxie et al, reported PE rate of 5.1% (7/137) in consecutive series of 137 arthroplasty for fracture 16 . For proximal humerus ORIF, Nayar et al, in another registry study reported VTE rate of 3.0% and also reported a 0.36% VTE for fractures around distal humerus/ elbow 18 . Thus, proximal humerus fracture surgery can be considered major concerning VTE risk.…”
Section: Question: 1 - Concerning Vte Risk Which Surgeries Can Be Con...mentioning
confidence: 95%
“… 11 Additionally, total joint arthroplasty literature has demonstrated a lower incidence of postoperative DVT in patients receiving total intravenous anesthesia versus general or combined spinal epidural anesthesia for total knee arthroplasty (4.48% vs 15.87 and 14.93, respectively [ P 0.05]). 30 Although a much rarer occurrence in patients with upper extremity trauma versus lower extremity trauma, the rate of VTE following upper extremity fractures ranges from 0.95% in the distal radius/ulna to 3.0% in the proximal humerus, 31 representing a clinically significant complication. In patients with a traumatic insult, undergoing potentially lengthy surgery, who are also COVID-positive, and thus, in a hypercoagulable state, the surgeon must have a low index of suspicion for thrombotic complications and consider using a method of anesthesia that mitigates this risk .…”
Section: Preoperative Considerationsmentioning
confidence: 99%